Plan de marketing relacional para fidelizar los clientes de los bancos comunales de la Fundación ESPOIR regional los ríos oficina Quevedo, año 2015 - Parra Cortéz, Isabel Antonia (2015)
This research work was made in the Communal banks Espoir-My Foundation bankito Regional Rivers and information in the offices located in the canton Quevedo process, developed in 10 calendar months from the passage of the Bill in the year 2014. Was raised as a general purpose "Developing relationship marketing plan to retain customers of Community Banks of Rivers Regional Foundation office Quevedo, 2014". For the development of inductive research, deductive, investigative and statistical methods were used, plus techniques and instruments such as direct observation, interview aimed at employees and customers for diagnosis and research and population surveys was used to get general conclusions that contribute to the development of the proposal. Customers Foundation type credit Microcredit asking is, same as requested up to two loans with an amount being $ 500 each, what you value most is the ease that give them to present the requirements, a high percentage if you used the safe and the rest not because of the call center is bad. The external situation analysis with macro and micro characteristics, determined thet the Espoir Foundation, has certain limitations in their processes of customer loyalty, which is why we have designed a plan to build customer loyalty by implementing advertising strategies and innovation that contribute to good institutional development and be competitive in the market, is also sought for the loan payments is twentieth or monthly services and general feel is a customer through training systems improve employees Espoir Foundation